ATG8 Expansion: A Driver of Selective Autophagy Diversification?. (March 2017) - Kellner, Ronny; De la Concepcion, Juan Carlos; Maqbool, Abbas; Kamoun, Sophien; Dagdas, Yasin F.
Abstract : Selective autophagy is a conserved homeostatic pathway that involves engulfment of specific cargo molecules into specialized organelles called autophagosomes. The ubiquitin-like protein ATG8 is a central player of the autophagy network that decorates autophagosomes and binds to numerous cargo receptors. Although highly conserved across eukaryotes, ATG8 diversified from a single protein in algae to multiple isoforms in higher plants. We present a phylogenetic overview of 376 ATG8 proteins across the green plant lineage that revealed family-specific ATG8 clades. Because these clades differ in fixed amino acid polymorphisms, they provide a mechanistic framework to test whether distinct ATG8 clades are functionally specialized. We propose that ATG8 expansion may have contributed to the diversification of selective autophagy pathways in plants. Trends: Selective autophagy is an ancient membrane-trafficking pathway that is essential for cellular homeostasis. Selective autophagy involves engulfment of autophagic cargo within double-membrane vesicles called autophagosomes. Autophagosomes are decorated by ATG8, a ubiquitin-like protein conserved across eukaryotes that is expanded in higher plants. Selective cargo recruitment is mediated by autophagy receptors that interact with ATG8 via an ATG8 interaction motif (AIM). Specialization of autophagy receptors toward ATG8 variants contributes to selective autophagy. Although selective autophagy plays important roles in development and stress tolerance, the molecular mechanisms underlying selectivity are currently elusive in plants.